Traceability and transparency: enhancing sustainability and circularity in garment and footwear. Issue 1 (9th December 2022) - Rinaldi, Francesca Romana; Di Bernardino, Claudia; Cram-Martos, Virginia; Pisani, Maria Teresa
Abstract: This Brief Report on the sustainability and circularity of global fashion-value chains discusses the content and potential impact of Recommendation No. 46, "Enhancing Traceability and Transparency of Sustainable Value Chains in Garment and Footwear" developed under the auspices and approved by the United Nations Centre for Trade Facilitation and Electronic Business (UN/CEFACT) in April 2021. It is a key output from a project undertaken by the United Nations Economic Commission for Europe (UNECE) and currently being implemented by UN/CEFACT in collaboration with the International Trade Centre (ITC) and financed by the European Union. The COVID-19 pandemic has highlighted the weakness of opaque garment- and footwear-value chains that lack traceability or transparency for brands, suppliers, and consumers. The public health crisis also increased consumer awareness of sustainability and the need for sustainability information. Recommendation No. 46 starts to set global standards for traceability and transparency and this Brief Report highlights its potential benefits on garment- and footwear-value chains that include nudging single consumer behaviors, supporting broader societal inclusiveness, helping manufacturers to implement circularity, and offering governmental bodies new tools for guiding the sustainable transition and verifying its effectiveness.